Chapter Di lessico e altre quisquilie: autopercezione ed eteropercezione linguistica nel social networking - Gheno, Vera (Strumenti per la didattica e la ricerca, 2021)
Digital writing and handwriting are cognitively different activities; thus, it is interesting to verify what happens to the written language when it is conveyed through a keyboard and no longer a pen. On the Net, where the text is stripped of all non-strictly linguistic clues such as tone of voice, facial expression, proxemics, gestures, etc., written words assume a large part of the communicative burden: in other words, we are what we type. Despite this, it often seems that users are not fully aware of how much their linguistic choices affect the construction of their reputation on the net. In this contribution, we reflect on the current state of the typed Italian, trying to hypothesize some future strategies to improve the condition of millions of novice and unprepared users.